Sources of resistance in wheat and triticale against loose smut caused by Ustilago segatum tritici - A.S. GREWAL, S.S. KARWASRAJ; 1. KUMAR, V.C. SINHA, M.S. BENIWALI, S. NAGARAJAN, (Indian Phytopathology, 2002)
Loose smut (Ustilago segatum var. tritici) is an important disease of wheat in the northern belt of India. There has been an increase in the incidence of the disease in the past two decades. None of the commercial wheat varieties is resistant to this disease. Being internally seedborne, it is easily amenable to systemic fungicides as dry seed treatment, but due to the high cost of chemical seed treatment, breeding smut resistant varieties remains the ideal method to contain the disease. Wheat and triticale varieties were subjected to artificial testing against the loose smut pathogen during 1987-94 at the Ludhiana (Indian Punjab) and Hisar (Haryana) centres. Out of large number of entries tested (c. 1000), PBW65, HDR-70, VL421 and WL 410 were either free or only exhibited trace infection during the past 8 years. Nine CIMMYT lines also exhibited good smut resistance under Indian conditions.